2019
DOI: 10.1038/s41423-019-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-producing regulatory B cells restrain the T follicular helper cell response in primary Sjögren’s syndrome

Abstract: Increased numbers of T follicular helper (Tfh) cells have been implicated in the development of autoimmune diseases including primary Sjögren's syndrome (pSS), but how the Tfh cell response is regulated during autoimmune pathogenesis remains largely unclear. Here, we first found negative correlations between IL-10 + regulatory B (Breg) cell numbers and Tfh cell responses and disease activity in patients with pSS and mice with experimental Sjögren's syndrome (ESS). Moreover, we detected high expression of IL-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 51 publications
2
86
0
1
Order By: Relevance
“…Given the role of regulatory B cells in restricting cellular responses, we propose this B cell defect could contribute to the relapsing and remitting nature of the disease. Moreover, it has been shown that B cell-derived IL-10 is important in T follicular helper organization, and restricting excessive antibody responses via interaction with Tfh cells 56 , 57 . It is therefore tempting to speculate that these patients generate inappropriately inflammatory B-cell responses in lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of regulatory B cells in restricting cellular responses, we propose this B cell defect could contribute to the relapsing and remitting nature of the disease. Moreover, it has been shown that B cell-derived IL-10 is important in T follicular helper organization, and restricting excessive antibody responses via interaction with Tfh cells 56 , 57 . It is therefore tempting to speculate that these patients generate inappropriately inflammatory B-cell responses in lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-7-dependent activation of STAT5 contributes to Bcl6 repression [ 60 ]. The latest research shows that IL-10 suppresses the differentiation of Tfh cells in human and mice by promoting STAT5 phosphorylation [ 61 ]. He et al [ 62 ] demonstrate that the secreted protein extracellular matrix protein 1 induced by IL-6 and IL-21 in Tfh cells promotes the differentiation of Tfh cells by downregulating the level of STAT5 phosphorylation and upregulating Bcl6 expression.…”
Section: Statsmentioning
confidence: 99%
“…Recently, we reported a novel function of Bregs in modulating Tfh generation in patients with primary Sjögren’s syndrome (pSS) [128]. The decreased Bregs and increased Tfh cells were inversely correlated in both pSS patients and mice with experimental Sjögren’s syndrome (ESS).…”
Section: Regulatory B Cellsmentioning
confidence: 99%